Influence of bottom ash as a sand replacement material on durability of self-compacting concrete exposed to seawater - Putra Jaya, Ramadhansyah; Mohd Haziman, Wan Ibrahim; Ahmad Farhan, Hamzah; Norwati, Jamaluddin; Mangi, Sajjad Ali (Taylor's University, 2020)
Concrete strength and durability performance under marine environment have been considered as challenging issue for many decades because seawater contains aggressive salts and it could affect the service life of concrete structure that is expected for the marine environment, such as offshore, harbour and coastal structures. Therefore, this study investigated the strength and durability performance of self-compacting concrete (SCC) containing Bottom Ash (BA) exposed to seawater under wetting-drying cycles. The exposure period for seawater was considered up to 180 days. Concrete mix incorporated BA from 10% to 30% by weight of sand with fixed water to binder ratio 0.4 with superplasticizer to produce 40 MPa concrete at 28 days. The performance of SCC was evaluated based on compressive strength, rapid migration test and depth of carbonation test. SCC with 10% BA gives satisfactory compressive strength and exhibits good resistance to chloride migration rate and it gives around 4.5% reduction in carbonation depth as compared to control mix at 180 days. The microstructural study also indicated that 10% BA form well shape calcium silicate hydrate gel, which delivers adequate compressive strength development. It was concluded that 10% BA as a sand replacement was found to be optimum, provides satisfactory strength and durability performance.